The Chemopreventive Effects of The Combination Between Tea Leaf and Mandarine Peel Extract on Breast Cancer Cell - Ega Hida Prabowo; Rifki Febriansah (Universitas Muhammadiyah Yogyakarta, 2020)
The number of breast cancer patients is increasing high in the world. This study aims to determine the chemopreventive effect of a combination of ethanolic extracts of tea leaves and mandarin peel in silico and in vitro on T47D breast cancer cells. Extraction by the maceration method used ethanol solvent 70%. The research is an in silico molecular docking utilized software of Autodock Vina to determine the binding affinity of tangeretin compounds and Epigallocatechin gallate (EGCG) on HER-2 protein. The antioxidant test used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method to determine the antioxidant activity of the combination of tea leaf and mandarine peel (CTM) extract. The in vitro test used the method of 3-(4,5-dimethyltiazol-2-il) -2,5-diphenyltetrazolium bromide (MTT) to determine the value of IC50 fromCTM on T47D breast cancer cells. The result of this study showed that CTM had a vigorous antioxidant activity with an IC50 value of 83 μg/ml. CTM had a weak cytotoxic activity with an IC50 value of 1889 μg/ml. Molecular tethering results of tangeretin and EGCG compounds produced a docking score of -6.6 and -5.0 kcal/mol with docking score proportion consisting of -4.9 kcal/mol of original ligand, -6.1 kcal/mol of doxorubicin and -4.5 kcal/mol of 5-fluorouracil. CTM had potential as a chemopreventive agent based on the robust antioxidant activity data on T47D breast cancer cells and molecular docking on the HER-2 protein.